Penguatan UMKM di Desa Sumberjo Melalui Program 3P: Pembuatan Brand, NIB, dan Pendampingan Sertifikasi Halal - Abbas, Wandi; Amin, Asma; Rizky Prawira, Muhammad; Ramadhan Antuli, Rezky (Penerbit Goodwood, 2023)
Purpose: This research aims to discuss strengthening Micro, Small and Medium Enterprises (MSMEs) of Women Farmer Groups in Sumberjo Village through various programs, namely: Brand Creation, NIB Registration (Business Identification Number), and Halal Certification registration. Methodology/approach: This activity was conducted in Sumberjo village, Polewali Mandar district, focusing on the Women's Farmer Group. The form of implementing activities is carried out by carrying out various steps, namely socialization and direct assistance to the community. Results/findings: The results of the activity are solving partner problems by transferring science and technology in the form of socialization, workshops, and assistance in the form of 3P such as Brand Creation, Business Identification Number Registration, Assistance with halal product certification, Product Innovation Development, and, Digitalization training for managing MSME websites, financial report bookkeeping applications and market place and delivery of production equipment assistance to partners. Limitation: referring to UP2KKK's needs, service activities are limited and focus on branding issues, business registration numbers, and halal certification. Contributions: This activity has an impact on KWT Gemah Ripah related to the development of products of higher quality and in terms of product quantity.